Thursday

March 5, 2015

March 5, 2015

Posted by **Abbey** on Tuesday, April 13, 2010 at 6:52pm.

k(2k+1) +(4(k+1)-1) = (k+1)(2(k+1)+1)

k^2+2k+3 For the right side?

- Math -
**PsyDAG**, Wednesday, April 14, 2010 at 2:38pmNo, for right side:

(k+1)(2(k+1)+1) = (k+1)(2k+2+1) = (k+1)(2k+3) = 2k^2 + 5k + 3

**Answer this Question**

**Related Questions**

Math - I need to show that the right side equals the left side but I am having ...

math - The scale balanced when n+20=80 Suppose the left side becomes n+3 How can...

Math: Intro to Vectors - Left side = right side check type of question. x - (x...

Math - Hello, Having trouble with this one... Solve the inequality: (2x-3)(4x)+x...

Physics - A 60.9 kg climber is using a rope to cross between two peaks of a ...

Trig - Proving Identities: 2 columns (tan + cot)^2 = sec^2 + csc^2 I'm having ...

proof by mathematical induction - subject is PreCalulus. 2^(k+3) = and < (k+3...

Trig - The question is: Set up a 2 column proof to show that each of the ...

MATH - i need help filling this out! 4x-10=32-3x 4x-10+____=32-3x+22 ____-10+...

chem again - One more question- how do I balance this half-reaction in terms of ...